[FeFe]‐Hydrogenase In Vitro Maturation. (25th October 2022) - Pagnier, Adrien; Balci, Batuhan; Shepard, Eric M.; Broderick, William E.; Broderick, Joan B.
Abstract: The [FeFe]‐hydrogenase H‐cluster is a complex organometallic cofactor whose assembly and installation requires three dedicated accessory proteins referred to as HydE, HydF, and HydG. The roles of these maturases and the precise mechanisms by which they synthesize and insert the H‐cluster are not fully understood. This Minireview will focus on new insights into the [FeFe]‐hydrogenase maturation process that have been provided by in vitro approaches in which the biosynthetic pathway has been partially or fully reconstructed using semisynthetic and enzyme‐based approaches. Specifically, the application of these in vitro, semisynthetic, and fully defined approaches has shed light on the roles of individual maturation enzymes, the nature of H‐cluster assembly intermediates, the molecular precursors of H‐cluster ligands, and the sequence of steps involved in [FeFe]‐hydrogenase maturation. Abstract : The generation of an active [FeFe]‐hydrogenase (HydA), the most efficient enzyme for H2 production, requires the synthesis of a complex organometallic metal center, the H‐cluster, where the reversible reduction of protons to H2 occurs. In vitro HydA maturation systems involving the three maturation proteins HydE, HydF and HydG have contributed significantly to a better understanding of the activation mechanism of this fascinating enzyme.